USE OF BREAK EVENT POINT (BEP) ANALYSIS AT PT INDOFOOD CBP SUKSES MAKMUR Tbk PERIOD 2019-2023 - Angga Siswanto; Aldy Wiranata; Rahmawati; Farida Agustina; Muhammad Fauzan (MANKEU (JURNAL MANAJEMEN KEUANGAN), 2024)
Break Even Point (BEP) analysis is one of the important methods in evaluating a company's financial performance to determine the minimum sales level that must be achieved to avoid losses. This study aims to examine the application of the BEP method in PT. Indofood CBP Sukses Makmur Tbk during the 2019-2023 period, with a focus on determining BEP values, evaluating financial trends, and identifying operational efficiency. The research method uses a descriptive quantitative approach with secondary data analysis obtained from the company's financial statements for the last five years. The results of the study show an upward trend in fixed costs and variable costs, which has an impact on increasing the BEP value from year to year until it peaked in 2022 of IDR 42,150,629 million, before decreasing to IDR 40,118,079 million in 2023. This finding indicates that there are efforts to improve the efficiency of the company's operational costs. The novelty of this study lies in the longitudinal analysis of BEP trends combined with the evaluation of contribution margin efficiency. The resulting output is in the form of strategic recommendations for the company to maintain financial stability through optimal management of fixed and variable costs.